PELATIHAN BUDIDAYA DAN PENGOLAHAN TANAMAN SORGUM MANIS (Sorghum bicolor L. Moench) UNTUK PAKAN - Sriagtula, R.; ,, Yetmaneli; Aini, Q. (Buletin Udayana Mengabdi; Vol 24 No 2 (2025): Buletin Udayana Mengabdi, 2024)
The sorghum plant (Sorghum bicolor L. Moench) has not been widely cultivated by the people of Indonesia. Sorghum are multifunctional plants, among others as food, feed, and fuel. Community Service Activities (CSA) aim to increase community knowledge and skills in sorghum cultivation and post-harvest technology to support feed security. The CSA was implemented in Jorong Batang Sariak Nagari Katapiang, Padang Pariaman Regency, West Sumatra Province. The service was implemented using the counseling method, making sorghum cultivation demonstration plots, harvesting sorghum seeds, and processing sorghum stover into silage. Based on the activities that have been carried out, it can be concluded: (1)The community in Jorong Batang Sariak Nagari Katapiang has succeeded in making a cultivation demonstration plot for sweet sorghum varieties of Numbu, (2) The community processes sorghum seeds into flour for concentrate feed for cattle, (3) The community is skilled in processing sorghum stover into silage, and (4) After the CSA activity, the community maintained the sorghum plants and independently harvested and processed the sorghum stover. Keywords: Cultivation, Feed, Forage, Silage, Sorghum.